Educating Students about their Interest in the Profession – As a Pedagogical Problem - Avliyaqulov Talib Kholmurodovich (Researchparks Publishing, 2021)
In the article, the question of teaching schoolchildren to the profession is drawn to the pen as a pedagogical problem. It speaks about the theoretical and practical importance of educating students ' interest in the profession on the basis of technological (labor) education.